Contact Stresses between Two Cylindrical Bodies: Cylinder and Cylindrical Cavity with Parallel Axes – Part I: Theory and FEA 3D Modeling. (2015) - Brezeanu, Ligia Cristina
Abstract: This paper presents the results of a study carried out using the Finite Element Method, on the contact stresses between two bodies: cylindrical body in a cylindrical cavity. The results are compared, following the analysis, to the results calculated on basis of the relations in H. Hertz's theory. The analyzed situation is: cylindrical body of radius R 1 in a cylindrical cavity of radius R 2, both bodies having parallel axes.